Development and initial validation of integrative Islamic personality inventory - Ismail, Nik Ahmad Hisham; Tekke, Mustafa (AENSI Publications, 2015)
Background: The measures related to personality in Islam have yet extended their domains to Nubuwwa (prophethood) and self component. In addition, these measures are solely Islamic sources, not studied the integration with Western perspective . Objective: The purpose of this study is to identify the major domains of Islamic personality using the Western and Islamic sources. Results: it is to describe the development and factor structure of a measure used to assess them, and to test the internal consistency (Study 1), the retest reliability (Study 2), and convergent and discriminant validity of this research (Study 3) in three samples of university students from ten Turkish universities. Conclusion: The combined findings from three studies reported here provide initial evidence that Integrative Islamic Personality Inventory (IIPI) is reliable, valid, and can be used in further studies.